Prevalence of psychological distress and associated factors among adult tuberculosis patients attending public health institutions in Dire Dawa and Harar cities, Eastern Ethiopia - Tegegn Mulatu Ayana; Kedir Teji Roba; Myrla Obejero Mabalhin (BMC, 2019)
Abstract Background In developing countries, the prevalence of psychological distress was higher among tuberculosis patients. Patients with tuberculosis infection were more prone to psychological distress than peoples without tuberculosis. However, little studies were conducted on psychological distress among tuberculosis patients in Ethiopia, particularly in the Eastern Ethiopian health institutions. Methods Institution-based cross-sectional study design was conducted. Based on the TB burden, four hospitals and six health centers were selected from Dire Dawa and Harar cities. Socio-demographic factors, psychological distress, TB related stigma experience, and alcohol use data were collected by face to face interview while TB and HIV related variables collected from TB registration book. All TB patients from the first month of TB treatment initiation through 6 were consecutively interviewed by trained data collectors from January to February 2018. The collected data were entered into Epi Data Version 3.1 software and exported into SPSS window version 20 for analysis. Bivariate and multivariate binary logistic regression was carried out. All variables with P-value ≤0.25 were taken into the multivariate model. Crude and adjusted odds ratios with a 95% confidence interval were estimated, and variables with P-value less than 0.05 in the final model were taken as significant predictors of psychological distress. Results The prevalence of psychological distress among tuberculosis in this study population was 63.3% (95% CI: 58.1, 68.1). Being from rural residence (AOR: 1. 98; 95% CI: 1.01,3.86), co-infection TB- HIV (AOR: 2.15; 95% CI:1.02, 4.56), presence of at least one chronic disease (AOR:3.04; 95% CI:1.59,5.79), experience of stigma (AOR: 1.71; 95% CI:1.01, 2.90), Pulmonary and MDR-TB (AOR:2.53; 95% CI:1.50,4.28) and smoking cigarette (AOR:2.53; 95% CI:1.06,6.03) were associated with psychological distress. Conclusions In this study, almost two-thirds of the tuberculosis patients had psychological distress. Chronic disease morbidity, HIV-TB co-infection and experienced TB related stigma were associated with psychological distress. Attention should be given to chronic diseases including HIV/AIDS diagnosis and referring to chronic disease units to prevent the impact on mental health. Consideration should be given for psychological distress and linking moderate to severe form of the disease to the Psychiatric clinics to hinder its effects.